PENGARUH SIKAP KONSUMERISME SISWA TERHADAP PENGGUNAAN SHOPPE PAY-LATER DALAM PANDANGAN EKONOMI ISLAM (STUDI KASUS PADA SISWA SMAN DI KABUPATEN TANGERANG) - Anzaningtyas, Mita (Journal of Business Education and Social, 2022)
Shopee paylater is a feature found in the shopee application that uses the pay later principle. With these features, a person becomes more wasteful and has a consumerism attitude that is not good as a result of these features. This study aims to determine the effect of student consumerism on the use of shopee paylater in the view of Islamic economics (a case study on high school students in Tangerang Regency). This makes researchers want to find out more to students about "INFLUENCE OF STUDENTS' CONSUMERISM ATTITUDE TO THE USE OF SHOPEE PAY-LATER IN ISLAMIC ECONOMIC VIEWS (CASE STUDY ON STUDENTS OF HIGH SCHOOL IN TANGERANG DISTRICT)". The research method used is a qualitative method with a descriptive approach with a descriptive approach. conducted interviews to dig up information for 4 days interacting directly with informants.The subjects in this study were high school students equivalent in Tangerang Regency. The results of the study explain that in essence this feature causes consumptive behavior which can be a problem in the future. Therefore, many scholars still call this feature usury.